Cysteine tRNA acts as a stop codon readthrough-inducing tRNA in the human HEK293T cell line - Valášek, Leoš Shivaya; Kučerová, Michaela; Zeman, Jakub; Beznosková, Petra (RNA (New York, N.Y.), 2023)
Under certain circumstances, any of the three termination codons can be read through by a near-cognate tRNA; i.e., a tRNA whose two out of three anticodon nucleotides base pair with those of the stop codon. Unless programed to synthetize C-terminally extended protein variants with expanded physiological roles, readthrough represents an undesirable translational error. On the other side of a coin, a significant number of human genetic diseases is associated with the introduction of nonsense mutations (premature termination codons [PTCs]) into coding sequences, where stopping is not desirable. Here, the tRNA's ability to induce readthrough opens up the intriguing possibility of mitigating the deleterious effects of PTCs on human health. In yeast, the UGA and UAR stop codons were described to be read through by four readthrough-inducing rti-tRNAs-tRNATrp and tRNACys, and tRNATyr and tRNAGln, respectively. The readthrough-inducing potential of tRNATrp and tRNATyr was also observed in human cell lines. Here, we investigated the readthrough-inducing potential of human tRNACys in the HEK293T cell line. The tRNACys family consists of two isoacceptors, one with ACA and the other with GCA anticodons. We selected nine representative tRNACys isodecoders (differing in primary sequence and expression level) and tested them using dual luciferase reporter assays. We found that at least two tRNACys can significantly elevate UGA readthrough when overexpressed. This indicates a mechanistically conserved nature of rti-tRNAs between yeast and human, supporting the idea that they could be used in the PTC-associated RNA therapies.
Keywords: cysteine tRNA; RNA transferová Cys; Cysteine; Humans; RNA, Transfer, Tyr; RNA, Transfer, Trp; RNA, Transfer; RNA transferová Tyr; Codon, Terminator; readthrough-inducing tRNA; near-cognate tRNA; lidé; HEK293 Cells; translation; RNA, Transfer, Cys; cystein; RNA transferová; nesmyslný kodon; proteosyntéza; Codon, Nonsense; HEK293 buňky; Anticodon; Saccharomyces cerevisiae; Protein Biosynthesis; terminační kodon; RNA transferová Trp; stop codon readthrough; antikodon